Refleksi Filsafat Materialisme (Konsumtif) Yang Berlebihan di Kalangan Mahasiswa Ditinjau Dari Matius 6:19-21 - Gijoh, Christin Angelina; Simanjuntak, Gloria Stevany; Gulo, Rita Nirwana; Dakhi, Asti Prida Okraina; Nuban, Feni Maria (Jurnal Christian Humaniora, 2024)
This research explores excessive consumption behavior among students using a reflective approach to the philosophy of materialism in Matthew 6:19–21. Descriptive qualitative methods and text analysis are used to understand the impact of consumerist materialism on students. The research results show that consumer behavior leads to financial difficulties, educational disruptions, and affected social interactions. The analysis of Matthew 6:19-21 shows the importance of considering spiritual wealth in balancing material needs. The implications of this research underscore the need for the integration of financial management and the development of spiritual values in the educational curriculum, as well as the role of parents in helping students understand deeper values than just material possessions. Research suggestions refer to financial management education, enrichment of spiritual values, and awareness of the social impact of consumer materialism as an effort to develop a balanced lifestyle between material needs and spiritual values.